Sonochemical synthesis and characterization of the biphasic compound Na2Ti3O7/Na2Ti6O13 - Chaar, S. M.; Da Silva, J. P.; Nobre, F. X.; Passos, J.; Aguilera, L.; Silva, J. H.L.; Silva, R. S.; Guerrero, F.; Pontes, F. M. [UNESP]; Leyet, Y. (FapUNIFESP (SciELO), 2021)
This study processed and characterized the biphasic ceramics Na2Ti3O7/Na2Ti6O13that were obtained from semi-crystalline nanoparticles synthesized using sonochemical methods. Structural characterization techniques, such as X-ray diffraction and Raman spectroscopy, were used to identify the crystalline phases present. The Rietveld refinement revealed, among other structural parameters, the presence of two crystalline phases in compositions of 55.90% and 44.10% for sodium hexatitanate and trititanate, respectively. Via Raman spectroscopy, the presence of the main vibrational modes that correspond to the phases present in biphasic ceramics was confirmed. Finally, by using complex impedance spectroscopy, a decrease in the electrical resistance of both the grain (106Ω-104Ω) and its boundary (108Ω-105Ω) under increasing temperature was identified.
Keywords: Biphasic ceramics Na2Ti3O7/Na2Ti6O13; Complex impedance spectroscopy; Rietveld refinement; Sonochemical method